2022
DOI: 10.3390/f13081274
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Production and Carbon Sequestration Potential of Different Agroforestry Systems in India: A Critical Review

Abstract: Agroforestry systems (AFS) and practices followed in India are highly diverse due to varied climatic conditions ranging from temperate to humid tropics. The estimated area under AFS in India is 13.75 million ha with the highest concentration being in the states of Uttar Pradesh (1.86 million ha), followed by Maharashtra (1.61 million ha), Rajasthan (1.55 million ha) and Andhra Pradesh (1.17 million ha). There are many forms of agroforestry practice in India ranging from intensified simple systems of monocultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Our findings outlined that AGB, BGB, and total biomass yield were the highest in central Kashmir, followed by southern and northern Kashmir. Such a variation in biomass yields was reported to be correlated with the variation in carbon sequestration potential (CSP) [ 25 ]. Panwar et al [ 25 ] reported a high CSP in northern India (J & K as a whole state), associated with high biomass yields (AGB: 6.7–159.4 t. ha −1 ; BGB: 1.6–71.5 t. ha −1 ; total biomass yield: 15.9–202.6 t. ha −1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings outlined that AGB, BGB, and total biomass yield were the highest in central Kashmir, followed by southern and northern Kashmir. Such a variation in biomass yields was reported to be correlated with the variation in carbon sequestration potential (CSP) [ 25 ]. Panwar et al [ 25 ] reported a high CSP in northern India (J & K as a whole state), associated with high biomass yields (AGB: 6.7–159.4 t. ha −1 ; BGB: 1.6–71.5 t. ha −1 ; total biomass yield: 15.9–202.6 t. ha −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such a variation in biomass yields was reported to be correlated with the variation in carbon sequestration potential (CSP) [ 25 ]. Panwar et al [ 25 ] reported a high CSP in northern India (J & K as a whole state), associated with high biomass yields (AGB: 6.7–159.4 t. ha −1 ; BGB: 1.6–71.5 t. ha −1 ; total biomass yield: 15.9–202.6 t. ha −1 ). However, the study was very general and did not take into consideration the difference between Kashmiri regions in terms of vegetative populations nor site types (grazed, protected and seed-sown sites).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the fight against deforestation applies to climate action, human health, environmental stability, economic vitality and community resilience. The literature shows that agroforestry can act as a carbon sink in tropical forests (Panwar et al , 2022). The T03 report describes the Climate Smart Cocoa programme conducted in Ghana, which is also referred to in the literature as adequate to address deforestation, climate action and increase livelihood incomes (Nasser et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in developed countries, carbon inventories and data banks to monitor the carbon sequestration potential of different ecosystems still need to be prepared for the Indian sub-Himalayan region. Moreover, carbon sequestration studies for diverse land uses are scarce from this region [20,21,[28][29][30]. Such micro-level studies are essential for sustainable land use management for a country like India and especially for the Terai region of West Bengal to recommend suitable land use management prescriptions for carbon management meeting the local and national needs.…”
Section: Introductionmentioning
confidence: 99%